Підхід до визначення завантаженості трансмісії колісного трактора при впливі нерівностей поверхні - Кальченко, Борис Іванович; Чернявський, І. С.; Кожушко, Андрій Павлович (Харківський національний технічний університет сільського господарства ім. Петра Василенка, 2017)
В статті описано підхід до визначення завантаженості механічної трансмісії колісного трактора при впливі нерівностей поверхні. Наведено передаточні функції трансмісії з двома ведучими мостами, яка виконується за допомогою опису коливань моментів, що навантажують пружні ланки коливальної системи. Визначено передаточну функцію підвіски, яка описує плавність руху колісного трактора.

As you know, when driving on uneven ground wheel tractor wheels deformation occurs, which causes additional resistance movement and torque to the wheels. For fixed mode, torque developed by the internal combustion engine, equalises constant component of the reaction environment. Change of influence as rolling resistance moment acting on the wheel is in relation to transmission disturbance, defined oscillation system. The article describes the approach to determining the mechanical load wheel tractor transmission when exposed to surface irregularities. An gear transmission features two driving axles, which is performed by describing vibrations moments elastic load level oscillation system. Suspension defined transfer function that describes the smoothness of motion wheel tractor.
Approach to determining the load transmission wheeled tractor at effect of surface irregularities
Keywords: трактор колісний; завантаженість трансмісії; плавність руху; wheeled tractor; load transmission; smooth movement